2006
DOI: 10.1051/gse:2006019
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of two Y chromosome microsatellites in Chinese cattle

Abstract: -Two Y chromosome specific microsatellites UMN2404 and UMN0103 were genotyped and assessed for polymorphisms in a total of 423 unrelated males from 25 indigenous Chinese cattle breeds. Consistently, both microsatellites displayed specific indicine and taurine alleles in each bull examined. The indicine and taurine alleles were detected in 248 males (58.6%), and 175 males (41.4%), respectively, although these frequencies varied amongst different breeds examined. The indicine alleles dominated in the southern gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Seven loci used in the present study were found to be polymorphic, as reported in other studies (Budowle et al, 2005;Cai et al, 2006). The UMN0504 locus was found to be monomorphic in a previous study (Ginja et al, 2009) in which the same loci were also used.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Seven loci used in the present study were found to be polymorphic, as reported in other studies (Budowle et al, 2005;Cai et al, 2006). The UMN0504 locus was found to be monomorphic in a previous study (Ginja et al, 2009) in which the same loci were also used.…”
Section: Discussionsupporting
confidence: 68%
“…The 88 and 106 alleles were observed in only 1 animal of the SAR population. In the UMN0103 locus, zebu-specific alleles (136 and 125) were observed in the southern group and taurine-specific alleles (155 and 140) were observed in the northern group (Cai et al, 2006). In this study, the 126 allele of the UMN0103 locus was observed in all populations except for EAR.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In China, the prehistoric immigration of taurine cattle from the north and indicine cattle from the south left their traces in the present genetic landscape with a taurineindicine north-south gradient of both mtDNA and Y-chromosomes. 59 Occasionally, other bovine species contributed to the domestic gene pool. Yak (Bos grunniens) mtDNA was found in a Chinese cattle breed from Diqing.…”
Section: Box 1 Conservation Of Genetic Diversitymentioning
confidence: 99%
“…The DQ population inhabits the Diqing prefecture, whereas ZT is found in the Zhaotong prefecture. They have both adapted to temperate climates, and DQ has further adapted to high altitudes (2800–3300 m above sea level) (Nie et al ; Yu et al ; Cai et al ; Gou et al ).…”
Section: The Candidate Genes Are Associated With Heat Tolerance and Imentioning
confidence: 99%